The impact of uncertainty on disclosure of prenatal exome sequencing results: A vignette study among medical students - Jasmijn E. Klapwijk; Vyne Van der Schoot; Marike G. Polak; Stina Lou; Ida Vogel; Iris M. Jansen-Bakkeren; Karin E. M. Diderich; Katinka Dijkstra; Sam R. Riedijk (PLoS ONE, 2026)
Introduction We recruited medical students for a study to investigate how they make decisions regarding which hypothetical genetic results to report during pregnancy. We tested how medical students as healthcare professionals handled uncertain prenatal Exome Sequencing results, and whether intolerance of uncertainty (IU) influenced decisions to share results with prospective parents. Exploring the impact of uncertainty on important medical decisions can help optimize counselling. Materials and methods Fifty-one participants ranked vignettes covering several types of uncertain prenatal ES results on perceived uncertainty. Participants answered whether they would report each result to the theoretical couple and indicated how certain they were about their choice. Additionally, their IU was measured using the Intolerance of Uncertainty Scale (IUS) and results were compared between low IU and high IU to test whether this influenced the results. The role of termination of pregnancy (TOP) considerations on these variables and experienced anxiety was also explored. Results Participants reported fewer highly uncertain results than results low in uncertainty. Participants were more uncertain about their choices to report with highly uncertain results than results low in uncertainty. IU did not influence these relationships. Anxiety of the students when parents considered TOP was not correlated with number of reported results nor certainty with these reporting choices. Conclusions In this study we validated the widespread hypothesis that the willingness to convey uncertain prenatal ES results decreased as uncertainty increased. This willingness did not seem to be higher or lower when taking into account IU. More research among experienced healthcare professionals is needed to ascertain whether findings from this study extend to real-life decision-making.